The role of moral disengagement in the enjoyment of real and fictional characters. (22nd December 2011) - Krakowiak, K. Maja; Tsay, Mina
According to affective disposition theory, individuals continually monitor and judge characters' actions and form attitudes about characters based on these judgements. However, much entertainment content features characters that do immoral things. It has been proposed that individuals are able to like these characters despite their immoral behaviours through the process of moral disengagement. This study examined how the propensity to morally disengage and the fictionality of a narrative affected individuals' acceptance of immoral behaviours and their overall enjoyment of a narrative. Findings indicate that character liking mediates the relationship between moral disengagement and enjoyment. In addition, the propensity to morally disengage predicts actual moral disengagement, but moral disengagement is unaffected by the realness or fictionality of the narrative. Implications of the findings for entertainment research are discussed.